The Impact of Educandy Media on the Quality of Differentiated German Language Learning at SMAN 1 Sidoarjo - Arin Habibillah, Afifah; Pujosusanto, Ari (LATERNE, 2026)
This Study is motivated by the demands of the Merdeka Curicculum regarding the implementation of differentiated learning and the challenges faced by teachers in its application. One such challenge is the limitation of time and resources available to educators, as well as the selection of appropriate learning models or media that can accommodate the diverse learning characteristics of students. Therefore, this research aims to examine the influence of using the digital learning media Educandy on the quality of differentiated learning in German Language. The research employs a quantitative methodology, utilizing an experimental research design., involving 37 students of class XI-6 at SMAN 1 Sidoarjo as the object. Data collection was carried out using written pretest and posttest instruments of comparable difficulty, which were then analyzed using the T-Test to determine the significance of the difference in learning outcomes. The data analysis stages involved collecting the results of the pretest and posttest, and subsequently, the data was analyzed using Microsoft Excel. The analysis results indicate a significants increase in the quality of learning, evidenced by the improvement in the students average scores from 7-.27 during the pretest to 86.49 during the posstest. This study concludes that Educandy media provides a positive and significant influence on the quality of differentiated German Language learning, making it an effective medium to support learning strategies centered on individual student needs. Based on these research findings, it is recommended that the Educandy media be implemented/applied in diffetentiated learning.